Homeland security the possible, probable, and perils of information technology. - Kun, L.G (IEEE Engineering in medicine and biology magazine)
Information technology is a key component in both defending against and aiding terrorism threats. The author considers the background in making progress with technology, bioterrorism and other forms of terrorism, cybersecurity - national (and global) critical information infrastructure protection, and the possibility of the establishment of a new department, the Department of (National) Homeland Security. He concludes that, more than ever, coordination, cooperation, and integration become a fundamental must in order to optimize our resources, which calls for standardization and interoperability of resources.